THE MAIN PROPERTIES OF THE CONSTITUTIONAL AND LEGAL CONSOLIDATION OF THE PUBLIC AUTHORITY SYSTEM IN THE MODERN CONDITIONS OF CONSTITUTIONAL REFORM IN RUSSIA - Zenin, Sergey (Revista Inclusiones, 2020)
The purpose of this research is a comprehensive theoretical and legal analysis of the current state of constitutional and legal consolidation of the public authority system in Russia. Normative legal acts that mediate the implementation of constitutional reform in Russia, doctrinal sources, and significant foreign experience relevant to the subject of research have been studied. The following methods have been used: general philosophical, general scientific, special scientific, special. The main properties of the system of public authority system enshrined in the Constitution of the Russian Federation have been determined, considering such parameters as the features of building federal relations as the basis for the vertical delineation of functions and powers of public authorities, the state of the system of separation of powers in the context of the balance of checks and balances, and the degree of legal protection and independence of local self-government bodies. The constitutional reform, in terms of consolidating the system of public authority, made it possible to develop and strengthen the principle of subsidiarity in delimiting the subjects of jurisdiction and powers in the relationship between the bodies of state power of the Russian Federation and its constituent entities and to clarify the spatial limit of a state rule of the RF with the help of constitutional legitimation of federal territories. It created the basis for overcoming the "conflict of competence" between the state and municipal levels of power, ensuring the constitutional and legal balance between the branches of government at the federal level to prevent the development of non-systemic conflicts in the system of "checks and balances "and the emergence of constitutional crises of power.